Ion exchange properties of some new chelating resins from cresol urea formaldehyde - Luma T. Tuma (University of Thi-Qar Journal of Science, 2019)
Terpolymers resins( o,m,p –C UF) synthesized by the condensation of o,m,p- Cresol and Urea with Formaldehyde in the presence of acid catalyst , FTIR- spectroscopy and thermogravimetric analysis were used tocharacterize the terpolymers. Chelating ion exchange properties of these polymers were studied for Fe 2+, Cu 2+and Zn 2+ions. A batch equilibrium method was employed in the study of the selectivity of metal ionuptake . the study was carried out over a wide pH range and shaking time.The OUF and PUF terpolymers showedhighest selectivity for ions being studied.